The Impact of Family Relationships on Racial and Ethnic Identity Among U.S. Afro-Caribbeans - Amy Irby-Shasanmi; Akilah Hairston; Christy L. Erving (Socius)
Using the National Survey of American Life: Coping with Stress in the 21st Century, this study is guided by the following question: To what extent do family relationships (i.e., frequency of contact with, closeness to, and negative interactions with family) shape racial and ethnic identity among U.S.-born and foreign-born Afro-Caribbeans? The authors operationalize identity as closeness to Black Americans, closeness to Caribbean Blacks, and identity preference. The results indicate that closeness to family was associated with feeling close to Black Americans for U.S.- and foreign-born Caribbean Blacks. Second, closeness to family was associated with higher odds of closeness to other Caribbean Blacks, but only among foreign-born Afro-Caribbeans. Last, negative interactions with family was associated with adopting an ethnic identity instead of a racial identity for U.S.-born Caribbeans. For foreign-born Afro-Caribbeans, negative interactions with family was associated with lower likelihood of adopting an ethnic identity relative to an “other” identity. This study demonstrates the role of family relationships in understanding identity processes among U.S.- and foreign-born Afro-Caribbeans.